Comparative Analysis of Sensor Reading Accuracy Between Arduino and ESP32 Microcontrollers for TDS Sensor Measurements - Rahman, Abdul; Ulinuha, Agus (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to compare the performance of Arduino UNO and ESP32 microcontrollers in TDS sensor measurements, evaluating reading accuracy, response speed, and reading stability to recommend the most suitable microcontroller platform for water quality monitoring applications. Methodology: Tools & Hardware: TDS sensor, Arduino UNO (ATmega328P, 10-bit ADC), ESP32 NodeMCU (12-bit ADC), TDS meter (reference instrument). Methods: Waterfall methodology, literature review, direct observation, potentiometer testing, and voltage measurement. Water samples tested at 101, 201, 300, 406, and 515 PPM concentrations, each with three repetitions at room temperature ( 20–21°C). Main Findings: Arduino UNO achieved average voltage errors of 0.21%–2.12% across all TDS concentrations, compared to ESP32's 13.1%–54.32%. ESP32 misread 101 PPM as 48 PPM (54.32% error). Arduino UNO's standard deviation was 0.064 ADC versus ESP32's 2.019 ADC 31.5 times more variable confirming Arduino UNO's superior accuracy and stability for TDS sensor measurements. Novelty/Originality of this study: This Arduino UNO achieved average voltage errors of 0.21%–2.12% across all TDS concentrations, compared to ESP32's 13.1%–54.32%. ESP32 misread 101 PPM as 48 PPM (54.32% error). Arduino UNO's standard deviation was 0.064 ADC versus ESP32's 2.019 ADC — 31.5 times more variable confirming Arduino UNO's superior accuracy and stability for TDS sensor measurements.